2008
DOI: 10.1259/bjr/29507259
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative patient effective dose in cardiology

Abstract: Medical radiation from X-rays and nuclear medicine is the largest non-natural (man-made) source of radiation exposure in Western countries. The aim of this study was to assess the individual cumulative effective dose in patients admitted to our cardiology ward. We collected a cumulative radiological history from a structured questionnaire and access to hospital records in 50 consecutive adult patients (36 males; age, 66.7+/-10.8 years) admitted to the Institute of Clinical Physiology in Pisa. The cumulative ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 41 publications
3
57
1
1
Order By: Relevance
“…For men and women aged at least 60 years at the time of the first PCI, excess risk of potentially fatal cancers attributable to radiation ranged from 0.4% to 4% 26, 27. The number of PCIs is a risk factor for subsequent development of lung cancer28 and leukemia,23 and contributes to the majority of the significant radiological exposure of the adult cardiology patient 29. In a previous study in a much larger population of 16 311 in‐hospital cardiac patients admitted to our institution over the past 40 years, we showed that the cumulative estimated effective radiation dose from cardiologic testing was a significant predictor of cancer death and for (fatal and nonfatal) cancer onset 28…”
Section: Discussionmentioning
confidence: 99%
“…For men and women aged at least 60 years at the time of the first PCI, excess risk of potentially fatal cancers attributable to radiation ranged from 0.4% to 4% 26, 27. The number of PCIs is a risk factor for subsequent development of lung cancer28 and leukemia,23 and contributes to the majority of the significant radiological exposure of the adult cardiology patient 29. In a previous study in a much larger population of 16 311 in‐hospital cardiac patients admitted to our institution over the past 40 years, we showed that the cumulative estimated effective radiation dose from cardiologic testing was a significant predictor of cancer death and for (fatal and nonfatal) cancer onset 28…”
Section: Discussionmentioning
confidence: 99%
“…This objective is particularly important in cardiac imaging as, although the absolute radiation dose from an individual coronary angiography procedure might be relatively low, patients with cardiac disease often undergo multiple imaging procedures which can lead to substantial cumulative exposures [2].…”
mentioning
confidence: 99%
“…(14)(15)(16) We can indirectly estimate the effective radiation doses for the present study by converting the DAP values in the present study using the recommended conversion factor for cardiac ablation procedures. (17) When this conversion was done, we obtained an estimated effective radiation dose of 3.1 millisieverts (mSv) for patients with AVNRT who underwent ablation using CF.…”
Section: Discussionmentioning
confidence: 99%
“…Although these estimates are difficult to objectively quantify and interpret, any effective method to minimise radiation exposure is likely beneficial for both patients and medical staff. (13,14) Such considerations are important, especially when the advantages of NFS are weighed against its apparent excessive cost. The present study was not without limitations.…”
Section: Discussionmentioning
confidence: 99%